Awareness and Attitude towards Emergency Contraception (Sotang, Yearly Peer Reviewed Journal, 2020)
Globally, unintended adolescent pregnancies pose a significant burden. One of the most important tools that can help prevent unintended pregnancy is the timely use of emergency contraception (EC), which in turn will decrease the need for abortions and complications related to adolescent pregnancies. The objective of this study was to assess awareness and attitude towards emergency contraception among secondary level students. A descriptive cross sectional study was conducted in grade eleven and twelve students in Manmohan Memorial College in 2020 Jan-Feb purposively. Out of total population, 105 sample students were randomly selected. A self-administered semi-structured questionnaire was used to collect the data. Among 105 respondents, highest proportions (41%) of the respondents were aged 17 years. Majority (75.2%) of the respondents was aware that oral contraceptive pills can be used as EC method. Majority (65.7%) of the respondents replied I pill as EC available in Nepal. (65.7%) of the respondents stated that awareness program is needed to be promoted by government, (62.9%) of the respondents said that information about EC is needed to be provided by educational institutions, (42.9%) of the respondents disagreed that abortion is better than using EC. Based on the findings of the study it is concluded that higher secondary level students tends to have awareness and positive attitude towards EC.